2019
DOI: 10.3390/cells8020159
|View full text |Cite
|
Sign up to set email alerts
|

No Causal Effect of Telomere Length on Ischemic Stroke and Its Subtypes: A Mendelian Randomization Study

Abstract: Background: Epidemiological studies observing inconsistent associations of telomere length (TL) with ischemic stroke (IS) are susceptible to bias according to reverse causation and residual confounding. We aimed to assess the causal association between TL, IS, and the subtypes of IS, including large artery stroke (LAS), small vessel stroke (SVS), and cardioembolic stroke (CES) by performing a series of two-sample Mendelian randomization (MR) approaches. Methods: Seven single nucleotide polymorphisms (SNPs) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…One MR analysis showed conflicting results which shorter TL was marginally statistically significantly associated with the decreased risk of stroke [ 21 ]. Another two linear MR analysis provided no evidence of the linear association between genetically predicted short TL and IS as well as its subtypes [ 22 , 23 ]. Similarly, we also found null linear relationship between genetically predicted TL and IS risk in a Han Chinese population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One MR analysis showed conflicting results which shorter TL was marginally statistically significantly associated with the decreased risk of stroke [ 21 ]. Another two linear MR analysis provided no evidence of the linear association between genetically predicted short TL and IS as well as its subtypes [ 22 , 23 ]. Similarly, we also found null linear relationship between genetically predicted TL and IS risk in a Han Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…First, a MR study showed that shorter telomeres lead to a marginally significantly decreased odds of stroke in individual-level data [ 21 ]. Another two MR studies suggested that TL may be a marker of IS and its subtypes rather than a cause [ 22 , 23 ]. Two-sample MR typically assume that the exposure-outcome association is linear or log-linear [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, whether the association of IgG N-glycans with T2DM is the cause or consequence of the disease remains unconfirmed. Further cohort studies with longitudinal data (Cao et al, 2019a) or Mendelian randomization studies (Cao et al, 2019b) are warranted to monitor the changes in N-glycome through the whole course of T2DM, and so as to provide a more definitive explanation regarding the causal relationship between N-glycan profiles and T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…The high heterogeneity, particularly age difference, and reduced sample size might contribute the equivocal results of the subgroup analysis. Another meta-analysis based on causal inference approaches using TL-related SNPs as instrumental variables did not support the causal effect of shorter TL on ischemic stroke (36). It has to be noted that age, one of the most important covariates, was not considered in this study.…”
Section: Tl and Strokementioning
confidence: 98%